2013
DOI: 10.1177/0892705712473625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of accelerated weathering and termite attack on the tensile properties and aesthetics of recycled HDPE-pinewood composites

Abstract: Although wood-plastic composites (WPCs) are materials widely used in the construction industry, their durability constitutes a serious issue especially when used for outdoor applications. Therefore, this work gives account on the effect of biotic and abiotic degradation agents on two different WPCs prepared from recycled high-density polyethylene (HDPE) and pinewood residues. Two aspects were evaluated, namely mechanical properties and aesthetics. Compression-molded samples obtained from two different formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
(30 reference statements)
1
11
0
Order By: Relevance
“…They indicated that the coupling agent might have reinforced material resistance against termites due to a more resistant interface, which hindered the access of their mandibles into the lignocellulosic material. 30 The lowest mean mass losses caused by termites were observed in formulation 4B, 8B and 12B produced with recycled CCA-treated wood flour and 5% MAPE. In terms of termite mortality rates, the results indicate that recycled CCA and the addition of MAPE did not create statistically significant differences in any of the formulations tested in this study.…”
Section: Thermogravimetric Analysismentioning
confidence: 89%
“…They indicated that the coupling agent might have reinforced material resistance against termites due to a more resistant interface, which hindered the access of their mandibles into the lignocellulosic material. 30 The lowest mean mass losses caused by termites were observed in formulation 4B, 8B and 12B produced with recycled CCA-treated wood flour and 5% MAPE. In terms of termite mortality rates, the results indicate that recycled CCA and the addition of MAPE did not create statistically significant differences in any of the formulations tested in this study.…”
Section: Thermogravimetric Analysismentioning
confidence: 89%
“…and Bacillus sp . Lopez-Naranjo et al (2012) examined the effects of termite attacks on weathered and unweathered pinewood residue and recycled high-density polyethylene composites. It was observed that the termite species N. nigriceps was able to degrade compression-moulded specimens.…”
Section: Termite Biology and Their Distribution In Himachal Pradeshmentioning
confidence: 99%
“…), rubber products (Zhong & Liu ), synthetic films and plastic materials (López‐Naranjo et al . ), and food products.…”
Section: Termites As Structural Pestsmentioning
confidence: 99%
“…Termites harm many structures: bridges, dams, decks, homes (Gaju et al 2002;Manzoor & Mir 2010;Li et al 2011;Ab Majid & Ahmad 2015), surviving walls, roads, poles (Kumode et al 2013;Lenz et al 2013a), insulation of underground cables and pipes (Sternlicht 1977;Lenz et al 2013a). Damage is also caused to household furniture (Cosme et al 2018), paper (Jiménez-Francisco et al 2018, rubber products (Zhong & Liu 2003), synthetic films and plastic materials (López-Naranjo et al 2014), and food products.…”
Section: Termites As Structural Pestsmentioning
confidence: 99%